Protestant Restructuring in the Canadian City: Church and Mission in the Industrial Working-Class District of Griffintown, Montreal - Trigger, Rosalyn (Urban History Review / Revue d'histoire urbaine, 2002)
Increasing social and spatial segregation along class lines in nineteenth-century Montreal brought about a restructuring of the city's Protestant churches. This paper compares the strategies adopted by Anglicans and Presbyterians as they attempted to reorganize and improve their provision of church accommodation in the industrial working-class suburb of Griffintown between 1860 and the turn of the century. It demonstrates that while denominational responses to the changes taking place were strikingly similar in many respects, class differences within the working classes nevertheless resulted in a complex array of churches and missions, each catering to a slightly different niche within the community. It is argued Griffintown's places of worship not only came to reflect the transformation of class relations that emerged with industrialization but also created opportunities for the negotiation of these new relations within the religious sphere.